Struktur Populasi Genetik Ayam Hutan Hijau Menggunakan Sekuen Hypervariable 1 D-Loop DNA Mitokondria - M. Syamsul Arifin Zein; Sri Sulandari (Biota : Jurnal Ilmiah Ilmu-Ilmu Hayati, 2008)
Thirty-three individuals from four populations of green junglefowl (Gallus varius) were collected throughout Indonesia: 14 from Central Java, 4 from Eastern Java, 3 from Sumbawa island and 12 from Flores island. The mitochondrial DNA D-loop the samples were analysed for sequence diversity. Twenty-five haplotypes with 28 polymorphic sites were identified within the first hypervariable-1 fragment (397 bp) of the D-loop. Fu’s Fs value was -25.96 (all samples, P=0), indicating high genetic diversity and population expansion; a conclusion supported by a neighbor–joining analysis of the haplotypes. Though sample size per population varied between 3 and 14, the Fs values for the four populations, between -2.20 and -10.76, were all significant (P=0). Only one haplotype was shared between three populations (Central Java, Sumbawa island, and Flores island) by a total of seven individuals. Within populations, only three haplotypes were shared by three individuals. The remaining haplotypes were unique, indicating genetic differentiation between populations as confirmed by significant pairwise Fst values at P=0.05 in four out of the six population pairs (except two pairs of Central Java & Sumbawa island and Flores island & Sumbawa island). The diversity pattern observed at the mtDNA of the green junglefowl provides a baseline which may help to understand the recent population expansions of domesticated chickens from multiple centres of domestications. Our observations also suggest careful interpretation of the results of genetic characterization may be needed when applied to the management and conservation of species like the green junglefowl. As in other multiparous birds and mammals with a short reproductive interval, green junglefowl may have established distinct genetic entities in metapopulations across its geographic distribution.